METHODS OF DEVELOPING BASIC COMPETENCES OF PRIMARY CLASS STUDENTS WITH THE HELP OF GAMIFICATION: Xaitova Nazokat Fayzullayevna nxaitova@gmail.com - Xaitova, Nazokat (Журнал математики и информатики, 2024)
in this paper, the psychological aspect of the use of gamification is studied, the ways of forming students' basic competencies in the learning process through gamification are studied, ideas are given about activities to develop students' motivation through gamification, the expected result and criteria for its achievement.